The complete mitochondrial genome of Stratiolaelaps scimitus (Acari: Laelapidae) and the comparison of mitochondrial gene rearrangement in the Mesostigmata. Issue 8 (17th November 2019) - Mo, Weifen; Guo, Liuling; Xiao, Yi; Xin, Tianrong; Xia, Bin; Zou, Zhiwen
ABSTRACT: As an important predatory mite, Stratiolaelaps scimitus (Womersley) is commercially produced to control pests of edible fungi and greenhouse. In this study, the complete mitochondrial (mt) genome of S. scimitus was sequenced by Illumina HiSeq, which comparatively analysed all reported mt genome rearrangement of mesostigmatid species. The mt genome of S. scimitus was a typical circular molecule of 16, 468 bp (GenBank: MK912042) and contained the complete set of 37 genes as other metazoan mitochondrial genomes. The AT-and GC-skew on the majority strand was −0.061 and 0.365, respectively, which were reversed compared to those found in most metazoan mitochondrial genomes. Like other mesostigmatid mites, many gene rearrangements occurred in the mt genome of S. scimitus . The six mesostigmatid families containing rearranged mt genomes were characterized by unique gene order, except Diplogyniidae and Parasitidae. Shared gene clusters were found in four mesostigmatid families (Laelapidae, Blattisociidae, Phytoseiidae, and Macrochelidae), indicating that they are synapomorphic for these families. These gene characters are valuable in phylogenetic analysis of relationships at different taxonomic levels.